BAHASA INGGRIS - Sugiyanto, Sugiyanto; Tjahjono, Heru Kurnianto; Hartono, Arief; Khuluq, Lathiful (FEB - Universitas Lampung, 2018)
The research on comparative governance of non-profit organization (organisasi nir laba/ ONL) in case study on social welfare institution (lembaga kesejahteraan social/ LKS) of Mardi Wuto dan Hamba in Yogyakarta Indonesia aimed at finding out the difference of the governance model and practice of both LKS and the uniqueness of each LKS. LKS was one of non-profit organizations in Indonesia. The empirical data were obtained and the finding was described and interpreted based on qualitative case study. The interpretation was related to the normative expectation on the design and implementation of the management of both non profit organizations. The research finding of ONL Mardiwuto was that it had bureaucratic governance model indicated by the good interaction and relation of the stakeholders, as the value management stated on articles of association. Meanwhile, ONL Hamba had democratic governance model indicated by the very good interaction and relation of the stakeholders, beyond the value management stated on articles of association. The weakness of the research was that the sample was still limited. Then, for the future research, it was suggested that the sample would be more various, and the implication of the research was it could be a reflection material for the decision makers and the managers of ONL.